Indígenas no Espírito Santo: de sujeitos anônimos a agentes ativos nas disputas de poder entre os séculos XVI-XVII - Ghidetti, Gabriel Angra (2019)
From 1549, the social, cultural, economic and power relations that were constituted in Portuguese Brazil underwent significant modifications, beginning with the inauguration of the general government by Tomé de Sousa and the process of founding the administrative center in Bahia. At the same time, the arrival of the first Jesuit priests to the Brazilian lands. This was the case, similarly, in the Espírito Santo captaincy, a space that belonged to captaindonate Vasco Fernandes Coutinho. Thanks to the retrieval of letters, circulars and other information that was circulating within the Society of Jesus, a Catholic order also arrived that year with the first governor-general, Tomé de Sousa, we were able to carry out a reinterpretation of the sources that mentioned the contacts and the relationship between colonists, religious and the main characters of this dissertation: the Brazilian natives or, more specifically, the natives who lived in what was defined as the captaincy of Espírito Santo. This dissertation intends to raise new perspectives on the indigenous in the sixteenth and seventeenth centuries, beginning with the arrival of the Company's priests until the time that is usually defined as sugar wars, marked by strong tensions between Portugal and the nations of the after-sea, perceived by the Indians, who found themselves in the middle of a conflict that overflowed borders. To get from one end to the other, we carry out an analysis that wants to get away from traditional and factual history in order to establish itself as a narrative that praises not only the power relations that resulted from the struggle for the indigenous captive labor, but mainly to place the Indians in the center of the historical stage, where they could carry out moments of resistance of diverse natures.